Implementation of an attention training program with children with attention deficit hyperactivity disorder in South Africa - Wilson, Abigail Gillian (Department of Psychology, 2016)
Attention Deficit/Hyperactivity Disorder (ADHD) is a group of behavioural symptoms that include inattentiveness, hyperactivity and impulsiveness and tends to be the most commonly diagnosed childhood behavioural disorder. The aim of this study was to determine the feasibility of the Pay Attention! Intervention with a small group of children diagnosed with ADHD as compared to matched controls. The intervention focused on sustained, selective, alternating and divided attention. After a baseline evaluation, five children aged 6 to 8 years were assigned to receive bi-weekly Pay Attention! sessions for 12 weeks and five matched controls were assigned to a Test-only group. Participants completed an outcome evaluation approximately 12 weeks after their baseline evaluation, both of which included neuropsychological and behavioural (both parent and teacher) assessments. Results show that the intervention is feasible to administer and acceptable to participants. Although no significant treatment effects were found on the neuropsychological outcomes and for the teacher ratings of ADHD, there were however significant effects found on parent ratings of ADHD symptoms on the Child Behaviour Checklist and the Vineland Adaptive Behaviour Scale-II. These preliminary findings add to the growing body of literature on attention training interventions for children with ADHD. However, a randomised controlled trial is warranted to further investigate the specific use of the Pay Attention! intervention with this population in the South African context.